The development of national growth charts for Jordanian children aged 0–2 years - Al-Qerem, Walid; Bataineh, Lina; Jarab, Anan; Eberhardt, Judith; Alasmari, Fawaz; Hammad, Alaa (Frontiers in Pediatrics, 2025)
PurposeThis study aimed to determine the prevalence of underweight, overweight, and obesity among Jordanian infants aged 0–2 years, establish national growth reference charts, and compare the growth of Jordanian infants with the WHO growth standards.MethodsThe present study analyzed 260,027 anthropometric measurements derived from 82,874 healthy Jordanian children (51% boys) aged 0–24 months. These measurements included both cross-sectional and repeated entries, with each child contributing between one visit and nine follow-up visits (10 measurements). Weight and height measurements were analyzed using the Generalized Additive Models for Location Scale and Shape (GAMLSS) statistical method to develop the growth charts.ResultsSeparate models for height-for-age, weight-for-age, and weight-for-height were constructed for each gender. Significant discrepancies were found between WHO growth references and the Jordanian references. Children in Jordan were shorter, particularly among girls, and had slightly higher weight-for-age from the age of 7 months onward.ConclusionThe availability of Jordanian-specific growth references will improve the accuracy of assessing children's growth and enhance the monitoring and evaluation of their health and development.